Penggunaan Bahasa Jawa dalam Loka Drama Lara Ati karya Bayu Skak (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
Language has a very important role in life. Through language, humans can interact with each other both orally and in writing which aims to convey information. The form of interaction is not only in the form of direct communication but can also be in the form of indirect communication. As is the case with the interaction of a film which has the aim of conveying a message to its audience. Of the many films on YouTube, one type of film that is quite interesting is a regional language film, one of which is a Javanese language film. Javanese-language films also have a contribution in an introduction to the culture of a region. One of the newest films that uses Javanese and has language variations is the film Lara Ati by Bayu Skak. This research uses a theoretical approach in the form of a sociolinguistic approach and a methodological approach in the form of a qualitative descriptive approach. The data collection technique used is the observing and noting technique. The analysis technique uses a qualitative descriptive technique. The source of the data for this study is the Lara Ati Drama Workshop episodes 1 to 5 which are sourced from YouTube videos. The results of this study are the use of language that appears in the drama workshops in the form of Javanese, a variety of ngoko, krama and also a mix of languages. In addition, the characteristics that appear in the drama scene are language variations, namely dialect, speech level, code-switching and splitting. Based on the results of this study, there were errors in the use of the Javanese language based on the context. In addition, the characteristic forms that emerged were language variations including the Suroboyoan dialect and the ngapak dialect, the speech level of the Javanese language, the variety of ngoko lugu, ngoko alus, and krama lugu, krama alus, code mixing. -code switching, and splitting. Keywords: sociolinguistics; language variations; use of the Javanese language; lokadrama Lara Ati; Bayu Skak